Pelatihan Dan Pendampingan Akuntansi Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah (SAK EMKM) Bagi Pedagang Ikan di Pasar Depok Surakarta - Lilis Sulistyani,; Ifah Lathifah,; Ika Swasti Putri,; Eko Madyo Sutanto, (TAAWUN, 2022)
This service aims to provide training and accounting assistance based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) for Fish Traders in Depok Market, Surakarta. Training and mentoring activities for the accounting process based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) are carried out by means of presentations, discussions and simulations. The target of this Community Service activity is for Fish Traders at Pasar Depok Surakarta. The solution offered is that fish traders at Pasar Depok Surakarta as entrepreneurs will be able to compile simple financial reports based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This activity begins by assisting in making proof of transactions, the process of recording transactions to the preparation of financial statements. The expected results of this activity include fish traders in the Depok Surakarta market being able to record each transaction into transaction receipts, being able to carry out manual books related to the accounting cycle and compiling financial reports from their business results on the basis of SAK EMKM. The follow-up to this activity is that continuous guidance and mentoring will be carried out, so that mentoring participants can actually prepare simple financial reports based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) as well as training in the use of simple excel-based accounting software that makes it easier for fish traders. in the Depok-Surakarta market in preparing financial statements.